Determinants of Performance: A Case Study on Micro, Small, and Medium Enterprises in Kampar Regency - Novita Indrawati; Kurniawan, M. Taufik (APSSAI ACCOUNTING REVIEW, 2025)
Research aims: This study aims to determine the effect of the ability to prepare financial statements, entrepreneurial characteristics, innovation, and financial literacy on the performance of micro, small and medium enterprises (MSMEs) in Kampar Regency, Riau Province, Indonesia. Design/Methodology/Approach: The research method used is quantitative with a survey approach. The population in this study were all MSMEs in Kampar Regency, with a sample size of 150 MSMEs selected using accidental sampling technique. The data collection technique was carried out through distributing questionnaires directly to respondents. Data analysis uses multiple linear regression to test the effect of each independent variable on the dependent variable. Research findings:  The results showed that the ability to prepare financial statements, entrepreneurial characteristics, innovation, and financial literacy had a significant effect on the performance of MSMEs. Theoretical contribution/Originality: These findings emphasize the importance of increasing the capacity of MSME actors in terms of financial recording, entrepreneurial attitudes, innovation development, and understanding of financial literacy to support improved business performance. Practitioner/Policy implication: The study recommends that MSMEs need for training and mentoring for MSME actors in financial reporting, strengthening entrepreneurial spirit, enhancing innovation, and improving financial literacy to boost business performance.